An Efficient Countermeasure against Fault Sensitivity Analysis Using Hybrid Parallel S-boxes - Li, Qipeng; Zhou, Fang; Wu, Ning; Yasir (Lecture notes in engineering and computer science, 2017)
Fault Sensitivity Analysis (FSA) is one of the fault attacks which can threaten the security of cryptographic module equipped with conventional countermeasure. In this paper, we present an efficient countermeasure against FSA based on mask strategy and hybrid parallel S-boxes structure. The masked AES circuit with the hybrid parallel S-boxes structure was proposed. The hybrid parallel S-boxes structure is composed of random selectors and four kinds of mask S-boxes. The proposed countermeasure can destroy the relationship between the fault sensitivity and the input Hamming weight, but also destroy collisions among the fault sensitivity characteristics of S-boxes. We conduct two kinds of FSA attacks against the AES circuit implemented on Xilinx Spartan FPGA, and the results show that FSA cannot threaten the security of the AES circuit with proposed countermeasure.